Healing comparison of suturing flap repositioned and applying periodontal pack after the modified widman flap procedure / envelope technique - Witjaksono, Widowati; , Soekamto (Airlangga University Press, 2000)
The purpose of the present preliminary study was to asses macroscopically the healing comparison process after suturing flap repositioned and applying periodontal pack after the modified Widman Flap procedure (envelope technique). Experimental surgery was performed in anterior maxilla or the mandibular teeth. The surgical procedure involved the evaluation of a full thickness of mucoperiosteal flap, scaling and root planning to the base of the pocket, at the end of the surgery, the flaps were then replaced in two ways. One side was sutured and the other side was applied by periodontal packed. After aweek, the experimental area were checked for suture removal and assessing the recovery process. The result shows healing process after this flap operation did not show any significant difference between healing of sutured flap repositioned and applied periodontal pack only